2015
DOI: 10.1186/s12876-015-0352-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided sampling of solid pancreatic masses: 22-gauge aspiration versus 25-gauge biopsy needles

Abstract: BackgroundBiopsy needles have recently been developed to obtain both cytological and histological specimens during endoscopic ultrasound (EUS). We conducted this study to compare 22-gauge (G) fine needle aspiration (FNA) needles, which have been the most frequently used, and new 25G fine needle biopsy (FNB) needles for EUS-guided sampling of solid pancreatic masses.MethodsWe conducted a retrospective cohort study of all EUS-guided sampling performed between June 2010 and October 2013. During the study period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 31 publications
0
35
1
Order By: Relevance
“…The procurement of visible core was obtained in all cases in our [4,6,10,22]. Conversely, there is one paper showing a diagnostic rate of 34% based on core biopsy with a 22G needle and five passes [23].…”
Section: Discussionmentioning
confidence: 91%
“…The procurement of visible core was obtained in all cases in our [4,6,10,22]. Conversely, there is one paper showing a diagnostic rate of 34% based on core biopsy with a 22G needle and five passes [23].…”
Section: Discussionmentioning
confidence: 91%
“…EUS-FNA has a proven track record as a relatively safe procedure for sampling solid pancreatic lesions, with sensitivities and diagnostic accuracies in the range of 80% to 95%. [42][43][44] In a study evaluating pancreatic mass sampling via EUS-FNA with a 25-gauge needle compared with percutaneous ultrasound-guided CNB using an 18-gauge needle, Sur et al described no significant differences with regard to the accuracy, technical failure rate, sensitivity, or specificity between modalities; however, CNB had a significantly higher diagnostic yield (86%) compared with EUS-FNA (66%). 45 More recent advances in needle technology have enabled the endoscopist to obtain true tissue fragments comparable to CNB specimens from the minimally invasive endoscopic approach, such as the cutting reverse bevel EchoTip ProCore needle (Cook Medical, Bloomington, Ind) or the cutting SharkCore needle (Beacon Endoscopic, Newton, Mass).…”
Section: Pancreatic Lesionsmentioning
confidence: 99%
“…Although one study demonstrated the superiority of EUS-FNA using a 22-gauge needle compared with 22-gauge EUS-EchoTip ProCore biopsies of solid pancreatic lesions, 43 other publications have described superior diagnostic yield, more cellular cell blocks for ancillary testing, and more specific tumor characterization for EUS-EchoTip ProCore biopsies compared with EUS-FNA specimens. 42,44,46 Lung lesions Peripheral lung nodules are frequently sampled by computed tomography-guided percutaneous transthoracic sampling, either by FNA or CNB. As reflected in the recently published 4th edition of the World Health Organization classification for lung, pleura, thymus, and heart tumors, 47 the amount and type of information needed from these small biopsy specimens have evolved.…”
Section: Pancreatic Lesionsmentioning
confidence: 99%
See 2 more Smart Citations